Parallel recognition and classification of objects - Felice, Rodrigo (1999)
The development of parallel algorithms for an automatic recognition and classification of objects from an industrial line (either production or packaging) is presented. This kind of problem introduces a temporal restriction on images processing, a parallel resolution being therefore required. We have chosen simple objects (fruits, eggs, etc.), which are classified according to characteristics such as shape, color, size, defects (stains, loss of color), etc. By means of this classification, objects can be sent, for example, to different sectors of the line. Algorithms parallelization on a heterogeneous computers network with a PVM (Parallel Virtual Machine) support is studied in this paper. Finally, some quantitative results obtained from the application of the algorithm on a representative sample of real images are presented.